Ras association domain family protein 1a hypermethylation and PD-L1 expression in ovarian cancer: A retrospective study of 112 cases. (September 2019) - Zhu, Xinxin; Yang, Huixia; Lang, Jinghe; Zhang, Yan
Abstract: Objective: This study assessed the interrelationships between Ras association domain family protein 1a ( RASSF1A ) gene hypermethylation, PD-L1 protein expression, and the clinicopathological characteristics of 112 ovarian cancer (OC) samples. Methods: Formalin-fixed paraffin-embedded OC tissue samples from surgical resection were assessed. Bisulfite pyrosequencing and immunohistochemistry were applied to detect RASSF1A gene methylation and PD-L1 protein expression in tumor cells, respectively. RASSF1A gene methylation and PD-L1 protein expression levels were analyzed against clinicopathological features and prognosis through standard statistical methods. Results: Of the 112 OC samples, 49.1% (55/112) exhibited RASSF1A gene hypermethylation. The frequency of RASSF1A hypermethylation was significantly higher in nonserous subtype (73.0%), early stage (66.7%), and nonrecurrent OC (62.9%, p < 0.05). Among all samples, 61.6% (69/112) were positive for PD-L1 protein expression in tumor cells. No significant differences in PD-L1 expression were identified for age, menstrual status, histological type, tumor location, grade, stage, lymph node metastasis, or prognosis ( p > 0.05). RASSF1A methylation and PD-L1 expression were not correlated ( p > 0.05). Conclusions: This was the first study linking RASSF1A hypermethylation variability to PD-L1 expression and clinicopathological characteristics of OC. Epigenetic alteration of RASSF1A was closely associated with nonserous subtype, early stage, and nonrecurrent OC, indicating that RASSF1A hypermethylation may play a role in early detection of OC. Expression of PD-L1 had no relationship with the studied clinicopathological characteristics or RASSF1A hypermethylation in the 112 OC samples.